The Role of Journalism In Countering Hoaxes on Social Media For Journalism Students of the Class of 2022 in Bengkulu - Tobing, Christopher Dapotan Immanuel Lumban; Sari, Eka Vuspa (LPPPIPublishing, 2026)
The rapid development of social media has made it easier for people to access and share information. However, this condition also increases the potential spread of false information or hoaxes. Journalism students, as future journalists, have an important role in filtering and verifying information circulating on social media. This study aims to analyze the role of journalism in preventing the spread of hoaxes on social media among Journalism students of the 2022 cohort in Bengkulu. This research uses a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, interviews, and documentation. The results show that journalism students have a fairly good understanding of the definition and characteristics of hoaxes. Students are able to identify hoaxes through unclear sources, provocative headlines, and the absence of supporting data in news content. In addition, students demonstrate a critical attitude toward information on social media by conducting fact-checking before sharing information. Journalistic knowledge such as fact verification, information accuracy, and the use of credible sources also helps students filter information. However, there are still challenges such as the influence of viral information and the rapid flow of information on social media. Therefore, journalism students have an important role as agents of information literacy in educating the public about the importance of verifying information before sharing it.